PALEOMAGNETIC ANALYSIS OF CURVED THRUST BELTS REPRODUCED BY PHYSICAL MODELS - Costa E.; Speranza F. (My University, 2003)
This paper presents a new methodology for studying the evolution of curved mountain belts by means of paleomagnetic analyses performed on analogue models. Eleven models were designed aimed at reproducing various tectonic settings in thin-skinned tectonics. Our models analyze in particular those features reported in the literature as possible causes for peculiar rotational patterns in the outermost as well as in the more internal fronts. In all the models the sedimentary cover was reproduced by frictional low-cohesion materials (sand and glass micro-beads), which detached either on frictional or on viscous layers. These latter were reproduced in the models by silicone. The sand forming the models has been previously mixed with magnetite-dominated powder. Before deformation, the models were magnetized by means of two permanent magnets generating within each model a quasi-linear magnetic field of intensity variable between 20 and 100 mT. After deformation, the models were cut into closely spaced vertical sections and sampled by means of 1x1-cm Plexiglas cylinders at several locations along curved fronts. Care was taken to collect paleomagnetic samples only within virtually undeformed thrust sheets, avoiding zones affected by pervasive shear. Afterwards, the natural remanent magnetization of these samples was measured, and alternating field demagnetization was used to isolate the principal components. The characteristic components of magnetization isolated were used to estimate the vertical-axis rotations occurring during model deformation. We find that indenters pushing into deforming belts from behind form non-rotational curved outer fronts. The more internal fronts show oroclinal-type rotations of a smaller magnitude than that expected for a perfect orocline. Lateral symmetrical obstacles in the foreland colliding with forward propagating belts produce non-rotational outer curved fronts as well, whereas in between and inside the obstacles a perfect orocline forms only when the ratio between obstacles' distance and thickness of the cover is greater than 10. Finally, when a belt collides with an obstacle in the foreland oblique to the shortening direction the outer front displays rotations opposite in sign to oroclinal-type rotations, whereas the internal fronts seem to assume an ''oroclinal type'' rotational pattern. Furthermore rotation is easier in laterally unconfined models, i.e. when the wedge can ''escape'' laterally. The results from our models may be useful when compared to paleomagnetic rotations detected in natural arcs. In these cases, our results may allow for better understanding the tectonic setting controlling the genesis of curved mountain fronts, as is the case of the Gela Nappe of Sicily we compare with some of our models.